Kinetic Studies on the Destructive Action of Oxygen on Lyophilized Serratia marcescens - Dewald, Robert R. (1966)
Dried Serratia marcescens (ATTC strain 14041) cells were exposed to various partial pressures of oxygen and nitrogen. The colony-forming ability of the organisms was rapidly destroyed during exposure to oxygen but was unimpaired by exposure to purified nitrogen. The degree of inactivation depended upon temperature, time, and the partial pressure of oxygen, regardless of whether pure oxygen or dry air was used. The inactivation by oxygen followed the expression -1nN/N(0) = k[O(2)](1/3)t(1/2), where N(0) and N are the number of viable organisms before and after exposure respectively, [O(2)] is oxygen concentration, t is time, and k is the rate constant. At 25 C, k was 276 ± 36 moles(-1/3) cc(1/2) hr(-1/3) for oxygen pressures between 5.5 and 258 torr. In the temperature range between -78 and 40 C, the rate constant may be expressed as k = 10(5.95±04.2) exp[(-430 ± 26) cal/RT] moles(-1/3) cc(1/3) hr(-1/2).